2018
DOI: 10.5539/ijef.v10n3p56
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Interest Rate and Exchange Rate Volatilities on the Demand for Money in Developing Economies

Abstract: Volatilities in the interest rate and the exchange rate cause instability in money demand functions. This study investigates the effect of interest and exchange rates volatilities on money demand in developing countries using time series data of four African countries namely, Equatorial Guinea, Gambia, Nigeria and Uganda. The model used is a conventional log linear money demand function, with money demand specified as a function of income, interest rate, inflation rate, exchange rate, interest rate volatility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…During pre-crisis, industrial production in Korea was not responded due to the depreciation of yen against dollar but after crisis period industrial production significantly declined. Nyumuah, (2018) explained that exchange rate volatility and interest rate volatility did not significantly impact demand for money in developing countries. Money demand of these countries had unstable function.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…During pre-crisis, industrial production in Korea was not responded due to the depreciation of yen against dollar but after crisis period industrial production significantly declined. Nyumuah, (2018) explained that exchange rate volatility and interest rate volatility did not significantly impact demand for money in developing countries. Money demand of these countries had unstable function.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Bahmani and Bahmani-Oskooee (2012) concluded that exchange rate in Iran had long-run as well as short-run influence on demand for money. Nyumuah (2018) found that demand for money functions in developing countries were verified to be unstable and that was why the impact of interest rate and exchange rate volatility on the money demand function in the developing countries was insignificant. The study suggested that monetary authorities should have imposed the inflation targeting monetary policy and used rate of interest as a policy instrument.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This is a source of motivation in favor of the current research devoted to interpreting interest rate interaction between Bangladesh and the US. Nyumuah (2018) advocates inflation targeting monetary policy for the developing countries, and the nominal rate of interest has been suggested as the policy instrument. Using quarterly data on four African countries, the author draws a firm conclusion proposing inflation targeting as a monetary policy rule.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literatures on the effects of exchange rate changes on the demand for money in the Gambia are few and except for Nyumuah (2018), none included exchange rate in the demand function. Similarly, none of the studies use non-linear ARDL.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, none of the studies use non-linear ARDL. Nyumuah (2018) study the effect of an exchange rate change on four African countries that include the Gambia. The result indicates that on the whole exchange rate and interest charges do not have significant effects on the demand for money of the countries under study.…”
Section: Introductionmentioning
confidence: 99%